Dinamika dan Tradisi Kelompok Minoritas Budha Dalam Masyarakat Islam Melayu Palembang - Hamidah Hamidah (Medina-te : Jurnal Studi Islam, 2022)
This study aims to analyze how the dynamics and traditions of the Buddhist minority group in Palembang Malay Islamic society. The research method in this study basically uses descriptive qualitative research. The results of this study show that the dynamics of the Buddhist minority group in Palembang Malay Islamic society are dynamically related to group identities reinforced by religious and cultural identities in the form of ethnic identities, local tradition identities, and religious thought identities. The dynamics of relations can lead to harmony among Buddhists because of the factors that support this harmony. Where the owner of cultural identity makes a compromise which in the end makes cultural acculturation equally support the creation of balance in society. The adaptation strategy carried out by Buddhists in an effort to build harmony in their environment, through cultural strategies, namely acculturation, and building a dominant culture. The role of religious leaders in the development of Buddhism in Palembang, namely by building relations between religion and ethnicity, religion and religious thought, religion and the culture of the archipelago, religion and foreign culture. Deepen the practice of worship by carrying out rituals of prostration every day. Performing devotional service three times a day, giving dharma lectures after the devotional service. Apart from ordinary days, it is also carried out on religious holidays such as the anniversary of the birth of the Buddha and Bodisatva.